MISCONCEPTIONS OF RELIGIOUS MODERATION IN THE THEOLOGICAL DISCOURSE OF THE SALIB: A CRITICAL ANALYSIS OF THE INTERPRETATIONS OF QURAISH SHIHAB AND WAHBAH AZ-ZUHAILY - Hayati, Safira Malia (Jurnal At-Tibyan: Jurnal Ilmu Alqur'an dan Tafsir, 2022)
This article aims to discuss the misconception of religious moderation in the theological discourse of the cross in the Qur'an by using the interpretations of Quraish Shihab and Wahbah az-Zuhaily in QS. An-Nisa' verse 157. This verse is considered an accusation against the death of Jesus, and the Jews consider crucifixion as a form of humiliation that Jesus had to experience as a social disturbance. This study aims to analyze the interpretation of Quraish Shihab and Wahbah az-Zuhaily about the theology of the cross in QS. An-NisÄ' verse 157 and the exclusive values in their interpretation. This article is a literature review using the thematic method and a critical analysis approach to its interpretation. This study found that the interpretation of this two mufassir did not contain moderation values in their content, giving rise to an exclusive attitude in their interpretation. Meanwhile, this diversity in diversity is a challenge as well as a problem that must have a solution.